2018
DOI: 10.1515/hsz-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Protein crystallization in living cells

Abstract: Protein crystallization in living cells has been observed surprisingly often as a native assembly process during the past decades, and emerging evidence indicates that this phenomenon is also accessible for recombinant proteins. But only recently the advent of high-brilliance synchrotron sources, X-ray free-electron lasers, and improved serial data collection strategies has allowed the use of these micrometer-sized crystals for structural biology. Thus, in cellulo crystallization could offer exciting new possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 124 publications
0
75
0
1
Order By: Relevance
“…The structural determinants of macromolecular phase transitions are important to govern a wide variety of biological processes and disease states (1, 2). Microbial SLPs are highly expressed and ubiquitous proteins that self-assemble on the outside of bacteria and archaea to form crystalline protein coats (35).…”
Section: Introductionmentioning
confidence: 99%
“…The structural determinants of macromolecular phase transitions are important to govern a wide variety of biological processes and disease states (1, 2). Microbial SLPs are highly expressed and ubiquitous proteins that self-assemble on the outside of bacteria and archaea to form crystalline protein coats (35).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most in vivo crystals have a needle‐like shape, beside a few cubic‐rhomboid, hexagonal and bipyramidal morphologies reported till now and they are mainly located within the cytosol or inside membrane surrounded organelles like the endoplasmic reticulum, mitochondria, lysosomes and peroxisomes as shown in Figure . Details about in vivo crystallization and crystals observed in cellulo are also reported by Doye and Poon, Duszenko et al, Schönherr et al and Hasegawa …”
Section: In Vivo Crystalsmentioning
confidence: 63%
“…For more than a century it has been observed that protein crystallization occurs within living cells . In Table we summarize selected examples of in vivo protein crystallization together with their intracellular location inside different organism or cell systems.…”
Section: In Vivo Crystalsmentioning
confidence: 99%
See 2 more Smart Citations